Analisis Implikasi Hukum Dagang Terhadap Penggunaan Teknologi Blockchain Dalam Transaksi Dagang Internasional - Muhamad Afandimunir; Hudi Yusuf (CV. ITTC INDONESIA, 2024)
Over the past few years, blockchain technology has risen to prominence as a leading innovation in the realm of information technology. The potential offered by this technology in facilitating secure, decentralized, and transparent transactions has sparked significant interest in its application in the context of international trade. However, the use of blockchain technology in international trade also faces significant legal challenges. The objective of this research is to offer a comprehensive examination of the legal ramifications associated with the utilization of blockchain technology within the framework of international trade dealings. By considering aspects such as contract law, regulation, dispute resolution, and consumer protection, this research aims to provide a more comprehensive understanding of the legal complexities involved in the implementation of blockchain technology in international trade. Additionally, this study will also discuss the impact of blockchain technology on the processes of international trade transactions, including increased transparency, security, and efficiency. Various legal challenges encountered in the use of blockchain technology in international trade transactions will be analyzed, including the ambiguity of blockchain's legal status, the determination of appropriate regulations, and effective dispute resolution mechanisms. This study anticipates offering a deeper understanding of the intricate legal challenges inherent in employing blockchain technology within international trade transactions. By doing so, it aims to establish a foundation for crafting suitable regulations and fostering enhanced comprehension among industry participants. Consequently, this research is poised to significantly advance the adoption of blockchain technology, facilitating secure, transparent, and efficient international trade practices.